2022
DOI: 10.1017/beq.2021.52
|View full text |Cite
|
Sign up to set email alerts
|

The Ethics of Alternative Currencies

Abstract: Alternative currencies are means of payment that circulate alongside—as an alternative or complement to—official currencies. While these currencies have existed for a long time, both society and academia have shown a renewed interest in their potential to decentralize the governance of monetary affairs and to bring people and organizations together in more ethical or sustainable ways. This article is a review of the ethical and philosophical implications of these alternative monetary projects. We first discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Drawing on the conservation of resources (COR) theory, our study offered a different view of such conventional thinking and indicated that moral compensation effects did not necessarily occur because the mental resources losses caused by UPB prevented individuals from taking compensatory behaviors. Although some of the existing literature pointed out the complex links between ethical or unethical behavior in business and pro-environmental behavior ( Delmas and Burbano, 2011 ; Gamma et al, 2018 ; Larue et al, 2022 ), limited research has empirically examined the effect of UPB on pro-environmental behaviors in the workplace. This study empirically tested the relationship between UPB and pro-environmental behaviors and enriched the literature of green behavior in the workplace by illustrating employees’ UPB outcomes, which could deepen the knowledge and understanding of the negative effects of UPB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing on the conservation of resources (COR) theory, our study offered a different view of such conventional thinking and indicated that moral compensation effects did not necessarily occur because the mental resources losses caused by UPB prevented individuals from taking compensatory behaviors. Although some of the existing literature pointed out the complex links between ethical or unethical behavior in business and pro-environmental behavior ( Delmas and Burbano, 2011 ; Gamma et al, 2018 ; Larue et al, 2022 ), limited research has empirically examined the effect of UPB on pro-environmental behaviors in the workplace. This study empirically tested the relationship between UPB and pro-environmental behaviors and enriched the literature of green behavior in the workplace by illustrating employees’ UPB outcomes, which could deepen the knowledge and understanding of the negative effects of UPB.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-environmental behavior refers to behavior related to environmental sustainability that individuals engage in or lead and are conducive to the sustainable development of the ecosystem ( Peng et al, 2020 ). Relevant research has pointed out that there are complex relationships between ethical or unethical behaviors in organizations and pro-environmental behaviors and changes in the natural environment ( Delmas and Burbano, 2011 ; Gamma et al, 2018 ; Dong et al, 2022 ; Larue et al, 2022 ). For example, due to the hypocrisy effect on consumption choices, enterprise managers will formulate a large number of policies to motivate employees’ ethical behaviors, especially pro-environmental behaviors ( Yuan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Complementary currencies, also known as cryptocurrencies (Bellavitis et al, 2022; Kher et al, 2021), community currencies (Michel & Hudon, 2015), social currencies (Zelizer, 1998), local currencies (Gomez & Helmsing, 2008), or alternatives currencies (Larue et al, 2022), are alternative monetary systems that coexist alongside and complement fiat currencies, such as Brazilian Reais and Euros (Blanc, 2011; Lietaer et al, 2012). These currencies serve as a means of exchange and a unit of account within specific communities, defined by geographical, socioeconomic, or ideological criteria, facilitating the exchange of goods and services among community members (Meyer & Hudon, 2017).…”
Section: Theoretical Background: Complementary Currencies and Entrepr...mentioning
confidence: 99%
“…Establishing a dialog between the complementary currency and the entrepreneurship literature is therefore important to unlock the potential of using complementary currencies as an alternative monetary system in supporting and sustaining entrepreneurs. Taking an entrepreneurship perspective is also pertinent for exploring the practices and entrepreneurial uses of complementary currencies and their contribution to entrepreneurship and community development (Dissaux, 2023; Larue et al, 2022; Ruddick et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Conversation, 2 July. <https://theconversation.com/alternative-currencies-are-the-future-why-it-matters-for-development-80036> accessed 25 April 2023.27 Larue, L. andOthers (2022). The Ethics of Alternative Currencies.…”
mentioning
confidence: 99%